BACKGROUND: Squamous cell carcinoma originating from the oral cavity, lip, larynx and pharynx are grouped under head and neck squamous cell carcinomas (HNSCC). OBJECTIVE: To report on human papillomavirus (HPV) genotypes involved in HNSCC. STUDY DESIGN: A retrospective review of archival HNSCC specimens and patient demographic and clinical data accessioned between January, 2007 and December, 2009 in the Department of Pathology, Korle-Bu Teaching Hospital, Accra, Ghana. RESULTS: Cases from 58 males and 20 females included 29 from the oral cavity, 33 from the larynx, 11 from the pharynx and 5 from the parotid gland. HPV DNA was found in 15 (19.23%) of the tumors with 12 being HPV-16, 2 HPV-18 and 1 dual infection with HPV-16 and HPV-18, giving HPV-16 prevalence of 86.7%. Higher prevalence of HPV DNA was found in males than females. There was a trend towards subjects younger than 58 years being more likely to have HPV-positive tumors.The 15 HPV-positive cases were distributed in location as 8 of 33 (24.2%) from the larynx, 4 of 29 (13.8%) from the oral cavity, and 2 of 11 (18.2%) from the pharynx and 1 of 5 (20%) from the parotid gland. CONCLUSION: Oncogenic HPV infection was found in 19.23% of HNSCCs, with genotype 16 predominating. HPV-related HNSCC tended to occur at younger age compared to non-HPV-related HNSCC. The commonest site for HPV-associated HNSSC in Ghana is the larynx, rather than the oropharynx as reported in other studies. Host factors may be responsible for the site difference and more work is required to further elucidate this. - Kwansa-Bentum, B.; Aboagye-Antwi, F.; Otchere, J.; Wilson, M.D.; Boakye, D.A. (Parasites and Vectors, 2014)
Previous studies have shown a general reduction in annual transmission potential (ATP) of Anopheles species after mass drug administration (MDA) in lymphatic filariasis endemic communities. Whereas results obtained from a monitoring programme after three years of MDA revealed a decrease in ATP of Anopheles funestus this was not the same for An. gambiae s.s. in Ghana. In this study, the ability of these vectors in transmitting Wuchereria bancrofti in nine lymphatic filariasis endemic communities in Gomoa District of Ghana after four rounds of MDA with ivermectin and albendazole was investigated. Methods. After mass screening of inhabitants in these communities, twelve consenting volunteers with different intensities of microfilariae (mf) slept under partly opened mosquito nets as sources of mf blood meal. Hourly collection of mosquitoes and finger-pricked blood were taken from 21.00 to 06.00 hours the following day. For each hour, half of the mosquitoes collected were immediately killed and dissected for mf. The remaining half were maintained up to 13 days for parasite maturation. Parasitaemia and infection rates in the mosquitoes were determined by microscopy. The mosquitoes were identified by microscopy and molecular techniques. Results: A total of 1,083 participants were screened and the overall parasite prevalence was 1.6% with mf intensities ranging from 0 to 59 per 100 μl and geometric mean intensity of 1.1 mf per ml of blood. Of the 564 mosquitoes collected, 350 (62.1%) were Anopheles spp., from which 310 (88.6%) were An. funestus and 32 (9.1%) An. gambiae. Six anopheline mosquitoes (1.7%) were found infected with L1, but no larva was observed in any of the mosquitoes maintained up to 13 days. Molecular studies showed all An. gambiae s.l. to be An. gambiae s.s., of which 21 (70%) were of the M molecular form. Conclusion: At low-level parasitaemia after 4 rounds of MDA, there was no recovery of infective stage larvae of W. bancrofti in An. funestus s.l. as well as M and S forms of An. gambiae. © 2014 Kwansa-Bentum et al.; licensee BioMed Central Ltd.
Keywords: Anopheles funestus; Anopheles gambiae; Low-density microfilariae carriers; Mass drug administration; Wuchereria bancrofti